Coagulation Pathways, Hemostasis, and Thrombosis in Liver Failure - Intagliata, Nicolas M.; Davis, Jessica P.E.; Caldwell, Stephen H. (Seminars in Respiratory and Critical Care Medicine, 2018)
Achieving hemostasis, preventing and treating thrombosis, and laboratory measurement of the hemostatic pathways constitute the core elements of managing the critically ill patient with liver failure. Uncontrolled bleeding in acutely decompensated cirrhosis and acute-on-chronic liver failure is probably the most familiar clinical challenge to intensivists. Bleeding in these patients can be broadly divided into pressure-driven (portal hypertension-related) bleeding with only limited dependence on hemostatic pathways and intractable mucosal/wound bleeding, which is much more directly related to a severely disturbed hemostatic system with imbalances in the coagulation cascade and the fibrinolytic system. Both types of bleeding can occur simultaneously and may even coexist with inappropriate thrombosis such as portal vein thrombosis or venous thromboembolism. Due to the fundamental role of the liver in coagulation factor synthesis and its direct and indirect regulation of nearly all aspects of the hemostatic system, laboratory measurements of coagulation pathways also constitute key aspects of all prognostic scores that guide clinical decisions and forecast optimal interventions in both acute and chronic forms of liver failure.
Keywords: coagulation; bleeding; hyperfibrinolysis; cirrhosis; anticoagulation